Degradation of Plastic & Elastomers in Palm Oil based Biofuel - Leong, Jenifer Wei Yun (IRC, 2018)
Biodiesel is a way to reduce the usage of diesel, however the chemical reaction between biodiesel and storage materials might reduce the quality of the fuel. This research focuses on the degradation behaviour of plastics and elastomers when immersed in palm oil based biodiesel to investigate the suitability of materials to store biodiesel. Throughout this research, high-density polyethylene (HDPE), nitrile rubber (NBR), silicone rubber (SR) and ethylene propylene diene monomer (EPDM) are brought to focus as these materials are more commonly usedinindustrialespeciallyautomotivesectortostorebiodiesel. Toachievetheobjectives, static immersion will be carried out for 408h (approximately 3 weeks) by using B0, B7, B15 and B100 as immersing solution. After immersion test, observation and mechanical tests such as tensile testing and hardness test are carried out. HDPE is found with least changes no matter in physical or mechanical tests. Elastomers are more suitable to store B0 only instead of other biodiesel as its tensile strength and hardness decreases more than half as per received. It is concluded that the sequence of suitability to store biodiesel is as follow: HDPE, NBR, SR, and EPDM.